2015
DOI: 10.1002/mnfr.201400492
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa flavonoids protect hepatic cells against high‐glucose‐induced oxidative stress: Relevance of MAPKs

Abstract: Scope Oxidative stress plays a main role in the pathogenesis of type 2 diabetes mellitus. Cocoa and (‐)‐epicatechin (EC), a main cocoa flavanol, have been suggested to exert beneficial effects in type 2 diabetes mellitus because of their protective effects against oxidative stress and insulin‐like properties. In this study, the protective effect of EC and a cocoa phenolic extract (CPE) against oxidative stress induced by a high‐glucose challenge, which causes insulin resistance, was investigated on hepatic Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 56 publications
(165 reference statements)
12
84
0
Order By: Relevance
“…As antioxidants, CPE and EC also contributed to preserve cell functionality by protecting insulin‐resistant HepG2 cells against a high‐glucose induced oxidative insult . CPE and EC reduced ROS overproduction, highly prevented the alteration of the antioxidant defences (nuclear factor erythroid 2‐related factor and glutathione levels, and GPx and GR activities) and restrained signaling pathways related to stress namely MAPKs (ERK, JNK, and p38) .…”
Section: Antidiabetic Actions Of Cocoa Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…As antioxidants, CPE and EC also contributed to preserve cell functionality by protecting insulin‐resistant HepG2 cells against a high‐glucose induced oxidative insult . CPE and EC reduced ROS overproduction, highly prevented the alteration of the antioxidant defences (nuclear factor erythroid 2‐related factor and glutathione levels, and GPx and GR activities) and restrained signaling pathways related to stress namely MAPKs (ERK, JNK, and p38) .…”
Section: Antidiabetic Actions Of Cocoa Flavonoidsmentioning
confidence: 99%
“…As antioxidants, CPE and EC also contributed to preserve cell functionality by protecting insulin‐resistant HepG2 cells against a high‐glucose induced oxidative insult . CPE and EC reduced ROS overproduction, highly prevented the alteration of the antioxidant defences (nuclear factor erythroid 2‐related factor and glutathione levels, and GPx and GR activities) and restrained signaling pathways related to stress namely MAPKs (ERK, JNK, and p38) . Moreover, CPE prevented the impaired glucose uptake and the inhibition of the insulin transduction route from the first steps (p‐(Ser)‐IRS‐1/total IRS‐1 ratio) induced by a high‐glucose concentration through targeting MAPKs .…”
Section: Antidiabetic Actions Of Cocoa Flavonoidsmentioning
confidence: 99%
“…Several studies found that the polyphenolic compounds found in Aegle marmelos, Commiphora mukul, green tea, cinnamon and ginger have hepatoprotective properties in different animal models [Elgawish et al, 2015;Ismail, 2014;Ramesh et al, 2015;Suriyamoorthy et al, 2014]. HFD/STZ induction produces high glucose levels in diabetic mice [Li et al, 2014], leading to oxidative damage and induced hepatotoxicity [Berdja et al, 2016;Cordero-Herrera et al, 2015]. In this study, HFD/ STZ-induced diabetic model had signifi cantly (P<0.05) higher glucose levels than the normal control group.…”
Section: Discussionmentioning
confidence: 49%
“…Subsequently, to evaluate the protective effect of EC against a high glucose challenge, cells were preincubated for 24 h with 10 µM EC; then, the medium was discarded and fresh medium containing 30 mM glucose was added for additional 24 h. At the end of the treatment, cells were incubated with 100 nM insulin for 10 min to test the response to insulin and then cells were harvested. Cells exposed to high-glucose constitute a reliable hepatic model to study insulin resistance and steatosis (Cordero-Herrera et al, 2014, 2015aNakajima et al, 2000;Shang et al, 2008;Zang et al, 2004).…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…Moreover, it has been reported that metabolites derived from a proanthocyanidin-rich extract of cocoa decreased lipid synthesis and excretion in HepG2 cells (Guerrero et al, 2013). Different studies have also demonstrated that cocoa or its main components, such as EC, exert hypoglycaemic and hypolipidaemic effects on several animal models of diabetes and insulin resistance (Cordero-Herrera, Martín, Goya, & Ramos, 2015a;Matsuia et al, 2005;Mokiran et al, 2014;Ramos et al, 2008;Ruzaidi, Amin, Nawalyah, Hamid, & Faizul, 2005;Si et al, 2011). Moreover, cocoa and dark chocolate have been reported to improve insulin sensitivity and lipid profile in healthy humans and T2D patients, alleviating the atherosclerotic cholesterol profile (Baba et al, 2007;Grassi et al, 2008;Mellor, Sathyapalan, Kilpatrick, Beckett, & Atkin, 2010).…”
Section: Introductionmentioning
confidence: 96%